Bentuk Kerukunan Antar Umat Beragama di Dusun Kampung Sindu, Desa Sinduwati, Kecamatan Sidemen, Kabupaten Karangasem - I Komang Suastika Arimbawa (Sphatika: Jurnal Teologi, 2021)
Harmony has become an interesting issue that is discussed in the community, considering that lately many problems have arisen due to intolerance. However, things like that can actually be anticipated, and with a good family, everyone understands the nature of religion in a plural environment. The foundations that can fortify harmony must be, namely the principle of living in harmony and the principle of living with respect. Everyone has an important role to play in maintaining harmony between religious believers. Adaptation is carried out for a common goal, and with a common goal, they mingle with each other regardless of differences, so as to prevent conflicts between religious believers, so that a social order will be realized in society. Thus, members of the community are merged into a social system of society. However, within each one there is still something that is maintained within him, namely the religious principles they adhere to and the norms that they still maintain.